2014
DOI: 10.1016/j.ypmed.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A repeated cross-sectional study examining the school impact on child weight status

Abstract: ObjectiveThe aim of this study is to examine whether there is a differential impact of primary schools upon children's weight status.MethodsA repeated cross-sectional study was undertaken using five years (2006/07–2010/11) of National Child Measurement Programme data, comprising 57,976 children (aged 4–5 (Reception) and 10–11 (Year 6) years) from 300 primary schools across Devon, England. Examining each year separately, the schools were ranked according to their observed and residual (having accounted for scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Neighbourhood has been considered an important context in the child’s life. However, our previous research, and that of Procter et al [ 19 ], found cross-classification by neighbourhood to have little impact upon the results, and hence cross-classification was not undertaken in the present study [ 20 ].…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…Neighbourhood has been considered an important context in the child’s life. However, our previous research, and that of Procter et al [ 19 ], found cross-classification by neighbourhood to have little impact upon the results, and hence cross-classification was not undertaken in the present study [ 20 ].…”
Section: Methodsmentioning
confidence: 90%
“…We previously undertook an analysis replicating the methods proposed by Procter et al [ 19 ] across five years [ 20 ]. Although we were able to replicate their findings within any single year, each schools impact (value-added ranking) varied considerably across the five years [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 For our primary outcome measure of BMI SDS, we determined the number of schools required (assuming an average of 35 Year 5 children per school, with coefficient of variation of 0.5, and an ICC of 0.02) to detect a between-group difference in BMI SDS of 0.25 units at 24 months with 90% power, a two-sided 5% significance level, a standard deviation (SD) of 1.3 and adjusting for baseline BMI SDS (assuming within-child correlation of 0.8). We allowed for a conservative 20% loss to follow-up or missing data at 24 months.…”
Section: Sample Size Calculationmentioning
confidence: 99%